Gravitational Energy-Momentum Density in Teleparallel Gravity - De Andrade, V. C. [UNESP]; Guillen, L. C T [UNESP]; Pereira, J. G. [UNESP] (American Physical Society (APS), 2000)
In the context of a gauge theory for the translation group, a conserved energy-momentum gauge current for the gravitational field is obtained. It is a true spacetime and gauge tensor, and transforms covariantly under global Lorentz transformations. By rewriting the gauge gravitational field equation in a purely spacetime form, it becomes the teleparallel equivalent of Einstein's equation, and the gauge current reduces to the Møller's canonical energy-momentum density of the gravitational field.